The Intellectual Dynamism of the High Middle Ages. - Monagle, Clare (Knowledge Communities, 2021)
Constant J. Mews's groundbreaking work reveals the wide world of medieval letters. Looking beyond the cathedral and the cloister for his investigations, and taking a broad view of intellectual practice in the Middle Ages, Mews demands that we expand our horizons as we explore the history of ideas. Alongside his cutting-edge work on Abelard, he has been a leader in the study of medieval women writers, paying heed to Hildegard and Heloise in particular. Mews has also expanded our knowledge of medieval music, and its theoretical foundations. In Mews' Middle Ages, the world of ideas always belongs to a larger world: one that is cultural, gendered and politicized. The essays in this volume pay tribute to Constant, in spirit and in content, revealing a nuanced and integrated vision of the intellectual history of the medieval West.